Multidimensional global games and some applications - Dzsamila Vonnák (Hungarian Academy of Sciences, Institute of Economics, 2018)
I extend the standard global games framework by introducing an addition target on which agents can coordinate on. I compare this multidimensional case to the standard global games problem. Furthermore, I investigate the effects of consolidating the multiple targets. I find that introducing an additional option generates a negative strategic correlation between the options and thus weakens the coordination. However, unifying the options eliminates the endogenous correlation and thus restores the coordination. I also show two potential applications to be modeled by these kinds of games.
Keywords: C72; D84; 330; global games; coordination